Improving Police Performance through Human Resource Quality, Motivation, Discipline, and Organizational Culture - Andy Eka Apriyanto; Hafidulloh Hafidulloh; Endri Haryati (BALANCE: Economic, Business, Management and Accounting Journal, 2026)
The West Surabaya Police Department represents a police organization in an urban area with a high level of task complexity. It exhibits significant variation in personnel performance, with some members still receiving ratings in the "sufficient" or even "poor" categories. The performance of Polri members is a fundamental factor in realizing a professional, effective, and integrity-based law enforcement institution. This study aims to analyze the influence of human resource quality, work motivation, and work discipline on personnel performance, with organizational culture as a mediating variable. The research approach was quantitative, using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Data were collected from 70 respondents and analyzed to test validity, reliability, and structural relationships between variables. The results show that human resource quality, motivation, and work discipline have a significant influence on performance, both directly and indirectly through organizational culture. These findings emphasize the urgency of strengthening organizational culture to foster discipline, motivation, and human resource development, thereby improving police institutional performance